Impact of water transfer on socioeconomic drought in China: A new approach based on production and consumption - Junlin Qu; Changhai Qin; Jiaxuan Chang; Yong Zhao; Hao Wang; Fan He (Agricultural Water Management)
Studies and government decisions misestimate the extent of socioeconomic drought because the impact of virtual water flows on water resources is ignored. Considering the full demand for water resources, this paper evaluates the mitigation of socioeconomic drought by water transfer from a contrasting perspective of production and consumption. In 2017, the virtual water transfer volume at the national level was 162.7 Gm3, and the inter-basin diversion volume was 19.6 Gm3. The transfer of water in physical and virtual form is already more than 30 % of total water consumption. Due to the improvement of water use efficiency, agriculture virtual water flow was reduced to 115.6 Gm3 in 2017, compared with 120.4 Gm3 in 2007. Demand induced by purchase and consumption is a significant driver of water transfer. By importing products and services, the affluent east (Beijing, Tianjin, Shandong, Jiangsu, Guangdong, Zhejiang) indirectly draw a large amount of water from the backward central and western regions (Xinjiang, Heilongjiang, Inner Mongolia, Guangxi). In 2017, the proportion of imported virtual water in regional consumption water increased significantly, accounting for 75.7 % in Beijing, 58.9 % in Tianjin and 46.1 % in Zhejiang. At the same time, the export regions provide remote support to the import regions by consuming local water. The proportion of virtual water exports to local water intake is 54.4 % in Heilongjiang, 48.3 % in Xinjiang, and 27.4 % in Inner Mongolia. Due to the contribution of virtual water, the water consumption stress index increases significantly compared to the production water stress index in the importing region. Not only internally, the risk of drought in the importing regions is severely underestimated due to the neglect of external stresses in the exporting regions. Demand management and shared responsibility must be strengthened to redistribute freshwater by adjusting consumption structure and supply-chain relationships.